The effect of reconstruction algorithms (iterative versus filtered backprojection) on the diagnosis of single pulmonary nodules using Thallium-201 and Technetium-99m MIBI SPECT - Ambayi, Rudo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMed)--Stellenbosch University, 2004.